2002
DOI: 10.1177/01461672022811003
|View full text |Cite
|
Sign up to set email alerts
|

Language and the Bicultural Self

Abstract: In a study of bicultural individuals’ self-perceptions, Chinese-born students were randomly assigned to participate in either Chinese or English. Serving as controls, Canadian-born participants of either European or Chinese descent participated in English. The effects of the language manipulation paralleled findings in previous studies comparing East Asians to North Americans. Participants responding in Chinese reported more collective self-statements in open-ended self-descriptions, lower self-esteem on the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
225
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(258 citation statements)
references
References 41 publications
27
225
1
Order By: Relevance
“…Recent findings suggest that language-dependency effects are found not only in episodic memory, but also in self-construal (e.g., Ross, Xun, & Wilson, 2002) and in academic learning (e.g., Marian & Fausey, 2006). For example, Ross et al (2002) found that bilinguals differed in number of collective self-statements, self-esteem ratings, and cultural views when responding in their two languages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that language-dependency effects are found not only in episodic memory, but also in self-construal (e.g., Ross, Xun, & Wilson, 2002) and in academic learning (e.g., Marian & Fausey, 2006). For example, Ross et al (2002) found that bilinguals differed in number of collective self-statements, self-esteem ratings, and cultural views when responding in their two languages.…”
mentioning
confidence: 99%
“…For example, Ross et al (2002) found that bilinguals differed in number of collective self-statements, self-esteem ratings, and cultural views when responding in their two languages. For academic learning, Marian and Fausey (2006) found that bilinguals were better at remembering information (e.g., about history, chemistry, etc.)…”
mentioning
confidence: 99%
“…Studies using selfdescriptions (Ross, Xun, & Wilson, 2002) and questionnaires, such as the Twenty Statement Questions (TST; Kuhn & McPartland, 1954), have consistently revealed that Euro-Americans provide more information about the independent self, such as personal attributes and beliefs (e.g., "I am tall, intelligent, good-natured") and less information about the interdependent self (e.g., "I am a son, a student, captain of the baseball team) compared to Asians (Bochner, 1994;Trafimow, Tirandis, & Goto, 1991;Wang, 2001). …”
Section: Independent and Interdependent Self-conceptsmentioning
confidence: 99%
“…As a primary communications medium that conveys ideas and information between people (Crystal, 2006;Harley, 1997), language is the "product of culture" (Hamers & Blanc, 2003, p. 8) as well as the "key vehicle of culture" (Chien & Benerjee, 2002, p. 211), suggesting that a dream containing both one's first, native language and a secondarily acquired language could be a valuable source of information in understanding a bilingual immigrant's unconscious attitudes toward the two worlds that he or she inhabits. Indeed, Ross, Xun, and Wilson (2002) found that bilingual individuals have separate cultural identities activated by the language of the culture.…”
mentioning
confidence: 99%
“…Bilingual individuals often feel in waking life that they have two different identities (Burck, 2004;Pang, 2009;Pavlenko, 2006), and that they have International Journal of Transpersonal Studies 3 Dreaming in Two Worlds and Two Languages separate identities that are activated by the language of the different cultures represented by those (Ross, Xun, & Wilson, 2002). According to Berry (2001), cultural identity consists of the attitudes individuals have about themselves in relation to membership in their cultural group.…”
mentioning
confidence: 99%